Tinjauan Fikih Muamalah Terhadap Praktik Jual Beli Sayur Kol dengan Sistem Jizaf - Rizkian Hidayat; Wage Wage (UM Purwokerto Press, 2022)
This article aims to describe how the practice of buying and selling with the Jizaf System and how the fiqh muamalah reviews the practice of buying and selling cabbage with the Jizaf System in Gombong Village, Belik District, Pemalang Regency.The type of research in this article is case study research whose data sources are obtained from facts that occur in the community. The research subjects were religious leaders, community leaders, the Head of Gombong Village, and farmers and vegetable traders in Gombong Village. While the data collection techniques used are interviews, observation, and documentation, where the data collected will be analyzed qualitatively using descriptive methods. The results of this study indicate that the buying and selling of cabbage that occurs can be calculated mathematically to find out the overall price. Transactions that occur between the seller and the buyer are carried out mutually pleased when the contract is carried out at the beginning. Buying and selling with the Jizaf System is seen from the opinions of the Imam Madzhab scholars and the Sharia Economic Law Compilation has fulfilled both in terms of the pillars and conditions. So that buying and selling cabbage using the jizaf system in Gombong Village is allowed.